Relationship between depression and quality of life in patients with chronic diseases of a level I hospital in Lima East - Roque Afray, Missael Gabriel (2019)
The objective of this research is to analyze the relationship between depression and quality of lifein patients with chronic diseases of a Level I Hospital in East Lima. The present study is design, notExperimental, cross-sectional and correlational type. The instruments used for the measurement were:the Health Status Questionnaire SF36, which contains eight dimensions, and the Hamilton DepressionScale. The sample consisted of 61 patients with chronic diseases, of both sexes and with ages between20 and 80 years. The results showed a highly significant inverse relationship between depression andthe eight dimensions of quality of life, obtaining physical function (rho = -.331; p <0.01), physical role(rho = -.407; p <0.01), body pain (rho = -.448; p <0.01), general health (rho = -.467; p <0.01), emotionalrole (rho = -.518; p <0.01), social function (rho = -.537) ; p <0.01), vitality (rho = -.637; p<0.01) andmental health (rho = -.566; p <0.01). Therefore, it is concluded that the higher the levels of depression,the lower the quality of life in patients with chronic diseases in a Level 1 hospital in Lima East.